women and puranic tradition in india - Monika Saxena (Routledge, 2019)
This book analyses the diverse ways in which women have been represented in the Purāṇic traditions in ancient India – the virtuous wife, mother, daughter, widow, and prostitute – against the socio-religious milieu around CE 300–1000.